The effect of L-arginine on guinea-pig and rabbit airway smooth muscle function in vitro - Perez, A. C. [UNESP]; Paul, W.; Harrison, S.; Page, C. P.; Spina, D. (Associação Brasileira de Divulgação Científica (ABRADIC), 1998)
We have investigated the effects of L-arginine, D-arginine and L-lysine on airway smooth muscle responsiveness to spasmogens in vitro. Both L-arginine and D-arginine (100 mM) significantly reduced the contractile potency and maximal contractile response to histamine but not to methacholine or potassium chloride in guinea-pig epithelium-denuded isolated trachea. Similarly, the contractile response to histamine was significantly reduced by L-arginine (100 mM) in rabbit epithelium-denuded isolated bronchus. The amino acid L-lysine (100 mM) failed to significantly alter the contractile potency of histamine in guinea-pig isolated trachea (P>0.05). In guinea-pig isolated trachea precontracted with histamine, both L-arginine and D-arginine produced a concentration-dependent relaxation which was not significantly altered by epithelium removal or by the presence of the nitric oxide synthase inhibitor, NG-nitro L-arginine methyl ester (L-NAME; 50 µM). Thus, at very high concentrations, arginine exhibit a non-competitive antagonism of histamine-induced contraction of isolated airway preparations that was independent of the generation of nitric oxide and was not dependent on charge. These observations confirm previous studies of cutaneous permeability responses and of contractile responses of guinea-pig isolated ileal smooth muscle. Taken together, the data suggest that high concentrations of arginine can exert an anti-histamine effect.
Keywords: L-Arginine; D-Arginine; L-Lysine; histamine; H1 receptors